Riflessioni su una tecnica politica della lingua in Benjamin - Palma, Massimo (Rivista Italiana di Filosofia del Linguaggio, 1970)
This article intends to approach Benjamin’s philosophy of language, with specific reference to his political philosophy. Young Benjamin’s fragments on language and knowledge have made it possible for him to build up a philosophicalhistorical perspective on the decadence of language after the Fall. Such decadence, according to Benjamin, has led to a conventional way of speaking and, at the same time, it has made it possible for myth rules – the eternal repetition of the same – to become law. Benjamin’s chief political essay, For the Critique of Violence, harshly distinguishes between law and justice, Recht and Gerechtigkeit. There is apparently no mediation between the two domains. This essay intends to put such a void of mediation into question. It thus interrogates Benjamin’s language fragments, looking for a different, political communication, which may be set in the space, which was opened, after the Fall, by the genesis of meaning and judgement. To criticize language with reference to its nominalistic origins means to move oneself and to act in the reign of history and semantics, as well. Such a movement could be defined as political, as Benjamin’s interpretation of Karl Kraus’ technique shows.